A Induksi pertumbuhan tunas anggrek (Dendrobium sp.) dengan pemberian BAP dan ekstrak jagung manis (Zea mays L.) - Harahap, Fauziyah; Sitepu, Rehlitna Fransiska; Edi, Syahmi; Suriani, Cicik; Daulae, Abdul Hakim; As, Mansur; Febrian, Didi; Subaedah, Sitti (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p14, 2024)
This study aims to determine the effect of the combination of BAP and sweet corn extract on the formation of shoots as an effort to propagate Dendrobium sp. This study used a factorial completely randomized design (CRD) with two factors. The first factor is the concentration of BAP which consists of 4 levels, namely B0 : 0 ppm, B1 : 1 ppm, B2 : 2 ppm, B3 : 3 ppm and the second factor is the concentration of sweet corn extract which consists of 4 levels, namely J0 : 0 gr/l , J20 : 20 gr/l, J40 : 40 gr/l, J60 : 60 gr/l. There were 16 treatment combinations and each treatment was repeated 3 times to obtain 48 experimental units. Data on the emergence of shoots and roots were analyzed descriptively. Data on the number of shoots, number of leaves, plantlet height and number of roots were analyzed by Analysis of Variance (ANOVA) and if they were significantly different, further tests would be carried out with the Duncan Multiple Range Test (DMRT) at 5% level. The results showed that the interaction between BAP and sweet corn extract had a significant effect on the number of shoots, number of leaves, plantlet height, and number of roots. The best results for the average number of shoots and leaves in the B2J60 treatment were 4.67 shoots and 15.67 leaves. The best results for the average plantlet height in the B1J60 treatment were 3.77 cm. The best result for the average number of roots in the B2J40 treatment was 8.33 roots .